2017
DOI: 10.21037/jtd.2017.05.21
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive aortic valve replacement in high risk patient groups

Abstract: Minimally invasive aortic valve replacement (AVR) aims to preserve the sternal integrity and improve postoperative outcomes. In low risk patients, this technique can be achieved with comparable mortality to the conventional approach and there is evidence of possible reduction in intensive care and hospital length of stay, transfusion requirement, renal dysfunction, improved respiratory function and increased patient satisfaction. In this review, we aim to asses if these benefits can be transferred to the high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 71 publications
1
17
0
1
Order By: Relevance
“…MiAVR has shown reductions in pain, mechanical ventilation, blood transfusion requirement, sternal wound complications, atrial fibrillation and hospital length of stay (LOS) when compared to SAVR via complete sternotomy (2)(3)(4)(5). The clinical applicability of MiAVR has expanded from low-risk patients into higher risk cohorts as improved postoperative outcomes have been demonstrated (6). TAVI can likewise be performed via several access routes, including femoral, axillary and carotid arteries.…”
Section: Introductionmentioning
confidence: 99%
“…MiAVR has shown reductions in pain, mechanical ventilation, blood transfusion requirement, sternal wound complications, atrial fibrillation and hospital length of stay (LOS) when compared to SAVR via complete sternotomy (2)(3)(4)(5). The clinical applicability of MiAVR has expanded from low-risk patients into higher risk cohorts as improved postoperative outcomes have been demonstrated (6). TAVI can likewise be performed via several access routes, including femoral, axillary and carotid arteries.…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive approaches reduced the amount of blood loss, probability of infection and hospitalization duration; improved cosmetic results; and accelerated patient recovery [ 10 , 11 , 12 , 13 ]. Despite the numerous advantages inherent to minimally invasive techniques, some authors have noted several negative effects, such as longer aortic cross-clamp and cardiopulmonary bypass times [ 12 , 13 , 14 ], which could in turn influence surgery performance and could be an unfavorable factor for patients of advanced age [ 15 , 16 ]. Moreover, some studies have explored short-term survival outcomes of minimally invasive techniques as compared with those of full sternotomy.…”
Section: Introductionmentioning
confidence: 99%
“…Studies, mostly observational, have shown potential benefits in terms of increased patient satisfaction, reduced wound infections, improved postoperative respiratory function, faster recovery, reduced blood transfusions and improved cost-effectiveness with MICS when compared to conventional approaches. [1][2][3] However, recently published randomised trials comparing mini-sternotomy aortic valve replacement (AVR) with conventional AVR have shown no clear benefit. [4][5][6] Randomised data looking at the potential benefits of mini-thoracotomy AVR are still awaited; however, some observational studies have shown that this holds a promise.…”
Section: Overviewmentioning
confidence: 99%